The Effect of Changing Climatic Conditions on the Morphological Traits and Chemical Composition of Almond Kernels - Slavica Čolić; Zorica Basić; Gordan Zec; Ivana Bakić; Dragan Rahović; Milica Fotirić Akšić; Violeta Mickovski Stefanović (Horticulturae, 2022)
This study evaluates the effect of two contrasting years, in terms of climatic parameters, on kernel morphology and content and on the composition of oil, tocopherols and the 11 macro- and micro-elements in almonds. Low precipitation and high temperatures increased the content of tocopherols, Cu and Zn but decreased the kernel ratio, the oil content, and the levels of macro-elements and of Cr, Fe, Mn and Mo. The obtained data indicate some statistically significant correlations among the kernel quality parameters and climate. A small variation in oil concentration with the highest value in ‘Texas’ (60.07%) was observed. The main tocopherol homologue was α-tocopherol (39.4 to 404.4 mg/100 g DW), representing more than 90% of the total tocopherols. Potassium was predominant (882.0 to 1104.5 mg/100 g), followed by phosphorus, magnesium, calcium and sodium. The most abundant micro-elements were iron (3.095 to 3.708 mg/100 g) and zinc (2.641 to 4.765 mg/100 g), followed by manganese, copper, molybdenum and chromium. The genotype 15/03 has the highest level of health-promoting compounds (α-tocopherol, potassium and zinc), so that, together with genotype 25/03 which showed the best response to changing climatic conditions, this genotype could be of interest for breeding programs.